2022
DOI: 10.1007/s11259-022-09991-8
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Supplementation enhances testicular volume and hemodynamics, reproductive hormones, sperm quality, and seminal antioxidant capacity in goat bucks under summer hot humid conditions

Abstract: Oxidative stress (OS) is brought on by heat stress (HS), which weakens antioxidant defense and initiates OS. Since mitochondria are the primary source of reactive oxygen species (ROS), HS-mediated OS may be lessened by targeting mitochondria with particular antioxidants. The purpose of this study was to investigate the effect of oral coenzyme Q10 (CoQ10) supplementation on the reproductive performance of goat bucks under HS conditions. Ten mature bucks were randomly separated into two groups and housed in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 70 publications
3
12
0
Order By: Relevance
“…The umbilical vein blood flow area pattern was almost flat with a slightly wavy margin during all weeks of gestation, in accordance with human [49,50] and veterinary medicines [51,52]. Similar to our current study, gestational age related to the marked decline in umbilical artery PI has been reported [53], which reflects placental villous circulation.in addition; there was an inverse relation ship between both doppler indices and blood flow velocity [53][54][55][56], Moreover, Wladimiroff et al [57] calculated mean RI values at different gestational ages among normal pregnant women. Therefore, noninvasive color and pulsed wave Doppler sonography have been used to evaluate uterine and umbilical blood flow changes during normal pregnancy during different gestational months at different ages, as the changes in these two parameters provide a picture of intrauterine fetal development, as previously mentioned in pregnant buffalos [58,59], sheep [60], queens [61], and bitchs [62].…”
Section: Discussionsupporting
confidence: 90%
“…The umbilical vein blood flow area pattern was almost flat with a slightly wavy margin during all weeks of gestation, in accordance with human [49,50] and veterinary medicines [51,52]. Similar to our current study, gestational age related to the marked decline in umbilical artery PI has been reported [53], which reflects placental villous circulation.in addition; there was an inverse relation ship between both doppler indices and blood flow velocity [53][54][55][56], Moreover, Wladimiroff et al [57] calculated mean RI values at different gestational ages among normal pregnant women. Therefore, noninvasive color and pulsed wave Doppler sonography have been used to evaluate uterine and umbilical blood flow changes during normal pregnancy during different gestational months at different ages, as the changes in these two parameters provide a picture of intrauterine fetal development, as previously mentioned in pregnant buffalos [58,59], sheep [60], queens [61], and bitchs [62].…”
Section: Discussionsupporting
confidence: 90%
“…Lipid peroxidation of the sperm membrane impairs sperm function and reduces fertility, due to altered sperm motility, decreased membrane integrity, damaged sperm DNA and formation of cytotoxic aldehydes. This oxidative stress is more pronounced following HS, which causes oxidative stress and apoptotic changes in sperm (El‐Sherbiny et al, 2022; Rizzoto & Kastelic, 2019; Shahat et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of testicular blood flow by the melatonin injection led to a mark in both Doppler indices parameters of the distal supra testicular arteries (PI and RI), which have a strong negative correlation with blood velocities parameters (PSV and EDV), testicular volume and intra-testicular colored areas[ 53 55 ]. The marked linear decline in both two Doppler indices leads to a substantial decrease in the blood flow resistance pattern and, therefore, an elevation of the testicular blood supply with an increase in sufficient nutrients and oxygen within both testes [ 56 60 ].…”
Section: Discussionmentioning
confidence: 99%